Are Custom Triflange Acetabular Components Effective for Reconstruction of Catastrophic Bone Loss? - Berasi, Carl C. (Clin Orthop Relat Res, 2014)
BACKGROUND: Although the introduction of ultraporous metals in the forms of acetabular components and augments has increased the orthopaedic surgeon’s ability to reconstruct severely compromised acetabuli, there remain some that cannot be managed readily using cups, augments, or cages. In such situations, allograft-prosthetic composites or custom acetabular components may be called for. However, few studies have reported on the results of these components. QUESTIONS/PURPOSES: The purposes of this study were to determine the (1) frequency of repeat revision, (2) complications and radiographic findings, and (3) Harris hip scores in patients who underwent complex acetabular revision surgery with custom acetabular components. METHODS: Between August 2003 and February 2012, 26 patients (28 hips) have undergone acetabular reconstruction with custom triflange components. During this time, the general indications for using these implants included (1) failed prior salvage reconstruction with cage or porous metal construct augments, (2) large contained defects with possible discontinuity, (3) known pelvic discontinuity, and (4) complex multiply surgically treated hips with insufficient bone stock to reconstruct using other means. This approach was used in a cohort of patients with Paprosky Type 3B acetabular defects, which represented 3% (30 of 955) of the acetabular revisions we performed during the study period. Minimum followup was 2 years (mean, 57 months; range, 28–108 months). Seven patients (eight hips) died during the study period, and three (11%) of these patients (four hips; 14%) were lost to followup before 2 years, leaving 23 patients (24 hips) with minimum 2-year followup. Sixteen patients were women. The mean age of the patients was 67 years (range, 47–85 years) and mean BMI was 28 kg/m(2) (range, 23–39 kg/m(2)). Revisions and complications were identified by chart review; hip scores were registered in our institution’s longitudinal database. Pre- and postoperative radiographs were analyzed by the patient’s surgeon to determine whether migration, fracture of fixation screws, or continued bone loss had occurred. RESULTS: There have been four subsequent surgical interventions: two failures secondary to sepsis, and one stem revision and one open reduction internal fixation for periprosthetic femoral fracture. There were two minor complications managed nonoperatively, but all of the components were noted to be well-fixed with no obvious migration or loosening observed on the most recent radiographs. Harris hip scores improved from a mean of 42 (SD, ± 16) before surgery to 65 (SD, ± 18) at latest followup (p < 0.001). CONCLUSIONS: Custom acetabular triflange components represent yet another tool in the reconstructive surgeon’s armamentarium. These devices can be helpful in situations of catastrophic bone loss. LEVEL OF EVIDENCE: Level IV, therapeutic study.